Insulin‐like growth factor 2 reverses memory and synaptic deficits in APP transgenic mice. Issue 10 (7th August 2014) - Pascual‐Lucas, Maria; Viana da Silva, Silvia; Di Scala, Marianna; Garcia‐Barroso, Carolina; González‐Aseguinolaza, Gloria; Mulle, Christophe; Alberini, Cristina M; Cuadrado‐Tejedor, Mar; Garcia‐Osta, Ana
Abstract Insulin‐like growth factor 2 (IGF2) was recently found to play a critical role in memory consolidation in rats and mice, and hippocampal or systemic administration of recombinant IGF2 enhances memory. Here, using a gene therapy‐based approach with adeno‐associated virus (AAV), we show that IGF2 overexpression in the hippocampus of aged wild‐type mice enhances memory and promotes dendritic spine formation. Furthermore, we report that IGF2 expression decreases in the hippocampus of patients with Alzheimer's disease, and this leads us to hypothesize that increased IGF2 levels may be beneficial for treating the disease. Thus, we used the AAV system to deliver IGF2 or IGF1 into the hippocampus of the APP mouse model Tg2576 and demonstrate that IGF2 and insulin‐like growth factor 1 (IGF1) rescue behavioural deficits, promote dendritic spine formation and restore normal hippocampal excitatory synaptic transmission. The brains of Tg2576 mice that overexpress IGF2 but not IGF1 also show a significant reduction in amyloid levels. This reduction probably occurs through an interaction with the IGF2 receptor (IGF2R). Hence, IGF2 and, to a lesser extent, IGF1 may be effective treatments for Alzheimer's disease.